Implementasi Penanaman Adab dalam Pembelajaran Jarak Jauh di Pondok Pesantren Tahfidzul Qur’an - Pebri Azhari; Uswatun Khasanah; H. M. Yunan Hidayat (Tahta Media Group, 2022)
This research is motivated by the problems of schools or educational institutions in general related to how to most effectively educate and teach students through the Distance Learning system, especially related to instilling etiquette and morals to students in Islamic boarding schools labeled tahfidz quran. In educating etiquette and morals in Islamic boarding schools, it is usually done by giving examples to the students at the boarding schools concerned. The purpose of this study was to find out how to implement the cultivation of adab and morals during the pandemic during distance learning at the tahfidzul quran Islamic boarding school and what are the supporting and inhibiting factors in inculcating adab and morals when learning using a distance learning system using qualitative research methods with a case study approach. From this study, it can be seen that the cultivation of adab and morals is still considered by the teachers even though learning uses a distance learning system. The cultivation of etiquette and morals is also supported by several work programs built by teachers during distance learning, such as material delivery, example, habituation of routines, discipline, and evaluation. And also found several supporting and inhibiting factors during the process of inculcating etiquette and morals through the distance learning system.